Biosorption of Vanadium ions from aqueous solution by acid modified and unmodified sour orange peels (Journal of the College of Basic Education, 2022)
Biosorption can be used as a cost effective and efficient technique for the removal of toxic heavy metals from wastewater using waste biomass derived from industries such as food processing. This study aimed to remedied vanadium (IV) ions from aqueous solution by batch adsorption system using both modified and unmodified sour orange peels (SORP) with a comparative investigation study. Optimization of Biomass, Time, Temperature, pH and Initial concentration parameters leads to the following results: metal ions adsorption onto the SOR biomass was established within 120 minute. The optimum pH for the metal binding to the biomass was found at pH=2, corresponding to the room temperature of 25C0, while maximum uptake was observed using an initial concentration of Vanadium equal to 100 ppm and 2gm of SOR biomass. These results indicate that modified and unmodified SORP sorbed more than eighty three percentage of the Vanadium ions. Confirmation of heavy metal ions binding with MSORP and UMSORP was achieved using Fourier Transform Infra Red Technique. Due to their low cost, good uptake capacity, and rapid kinetics, sour orange biomass is a promising biosorbent material warranting further study to release the environment from heavy metals contamination.